Relationship Between Demographic Characteristics, Knowledge of Antihypertensive Drug Use, and Health-Seeking Behavior Among the Elderly with Hypertension in Karawang Regency: Relationship Between Demographic Characteristics, Knowledge of Antihypertensive Drug Use, and Health-Seeking Behavior Among the Elderly with Hypertension in Karawang Regency - Salman Salman; Kurniati Nawangwulan; Yosi Meidiawati (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2026)
Hypertension in the elderly can reduce physical ability, daily activities, and psychological well-being, impacting quality of life. Factors related to the quality of life among the elderly with hypertension, such as demographic characteristics, knowledge of antihypertensive drug use, and health-seeking behavior, have been studied only to a limited extent at the primary healthcare level. This study aims to analyze the relationship between demographic characteristics, knowledge of antihypertensive medication use, and health-seeking behavior (HSB) with the quality of life among the elderly with hypertension in the service area of the Telukjambe Timur Community Health Centre in Karawang Regency. This study uses a quantitative approach with a cross-sectional design implemented in August-October 2025, with 68 respondents selected through purposive sampling. Data were collected using a structured questionnaire. Quality of life was measured using the WHOQOL-BREF, and HSB was assessed using a structured questionnaire developed based on the Andersen Behavioral Model. The analysis was descriptive and bivariate, using the chi-square test. The results showed that the majority of respondents had a good quality of life (76.5%). Knowledge of antihypertensive drug use (OR = 23.333; p = 0.001) and health-seeking behavior (OR = 12.600; p = 0.001) showed the strongest associations with quality of life among elderly with hypertension. These findings indicate that the quality of life of elderly with hypertension is related to their knowledge of drug use and active engagement in healthcare services. Education about antihypertensive therapy and the promotion of health check-ups at health facilities are strategies for supporting the quality of life among the elderly with hypertension.